Experiences from the epicenter: Professional impact of the COVID‐19 pandemic on genetic counselors in New York. Issue 1 (23rd November 2020) - Bergstrom, Katherine L.; Brander, Tehilla E.; Breen, Kelsey E.; Naik, Hetanshi
Abstract: The COVID‐19 pandemic disrupted the delivery of healthcare services, including genetic counseling. This study assessed the professional impact of the pandemic on genetic counselors (GCs) and evaluated how genetics service delivery models changed in New York State (NYS). One hundred sixty‐five NYS GCs participated in an anonymous survey. Clinic structure, telegenetics (video and/or telephone consultations) use and acceptability, and professional practices before and during the pandemic were compared. The most frequently reported consultation type shifted from in‐person only (49%) before the pandemic to telegenetics only (39%) during. Most were satisfied with video (93.1%) and telephone (81.4%) telegenetics. Additionally, 93.5% of participants expressed a desire to continue using telegenetics after the pandemic resolves. Common obstacles included difficulties coordinating sample collection (60.2%) and obtaining written consent for testing (57.6%). Billing methods for consultations during the pandemic did not change significantly. Participants were asked about NYS's lack of licensure, which restricts billing options. Most felt that genetic counseling licensure would benefit the profession (92.6%), the public (88.5%), and their institution/company (74.5%). This study provides insight into the effects of the rapid adoption of telegenetics and can guide future discussions about best practices for its use even after the health crisis resolves.